Psychometric validation of the Czech PLOC-R in high-school physical education - Harbichová, Ivana; Štochl, Jan; Scheier, Lawrence M.; Komarc, Martin (Frontiers in Sports and Active Living, 2025)
IntroductionThe Perceived Locus of Causality (PLOC) scale is widely used to assess motivation in physical education (PE), but no validated Czech version has been available. This study aimed to translate, adapt, and validate the revised PLOC (PLOC-R) in Czech high school students.MethodsA total of 2,967 students (mean age = 16.62, SD = 1.18) completed the Czech-adapted PLOC-R along with measures of psychological need satisfaction and PE engagement. Confirmatory factor analysis (CFA) tested its five-factor structure, while exploratory analyses identified problematic items.ResultsThe initial model showed moderate fit, but removing three items resulted in better factorial validity of the scale (CFI = 0.94, RMSEA = 0.06). Internal consistency was acceptable (ω = 0.78–0.90), except for external regulation (ω = 0.58). The scale demonstrated strict measurement invariance across gender and grade, and correlations with external variables supported its validity.DiscussionThis study provides the first validated Czech PLOC-R, enabling reliable assessment of PE motivation and facilitating cross-cultural comparisons.